Walking on broken glass: gender as predictor of job precariousness among young people in Spain - Solano Lucas, Juan Carlos (2021)
Previous evidence reveals that socioeconomic factors, such as contract duration, occupation, activity sector, age, training, nationality, marital status or gender, lead to precariousness. This research looks into the intersectionality of inequalities in order to explain the impact of precariousness among young people based on gender. Data from the Spanish Labor Force Survey (EPA) from 2005 to 2016 has been analyzed using logistic regression and hierarchical segmentation. Results suggest that the economic crisis has widened the gender gap in precarious jobs, such that currently, young women are more likely to face precarious situations as compared to young men.